Langkah-langkah Pengembangan Program Studi Kependidikan Islam Jurusan Tarbiyah STAIN Jember: Development Steps of the Islamic Education Study Program in the Tarbiyah Department of the State College for Islamic Studies (STAIN) Jember - Mundir Mundir (Fenomena, 2005)
The low market demand for the Islamic Education Study Program (Prodi Kependidikan Islam) at STAIN Jember necessitates strategic development to enhance its competitiveness and relevance. This study aims to identify essential steps for developing the program across the input, process, and output dimensions. Using a descriptive qualitative method with a developmental research approach, data were collected through observation, in-depth interviews, questionnaires, and documentation from purposively selected informants, including university leaders, department heads, lecturers, and students. The findings reveal seven strategic steps for input development, five for process improvement, and four for output enhancement. Key measures include intensifying socialization and collaboration with regional educational offices, designing a distinctive curriculum that emphasizes administration and management competencies, prioritizing lecturers with educational management backgrounds, expanding practical field experiences to include supervision and counseling, and formulating prospective political policies regarding graduate certification. The study concludes that program clarity regarding its orientation—whether producing teaching or non-teaching graduates—is fundamental, and recommends curriculum evaluation meetings and strategic diploma formatting to ensure graduate marketability. Rendahnya minat pasar terhadap Program Studi Kependidikan Islam (Prodi KI) di STAIN Jember memerlukan pengembangan strategis guna meningkatkan daya saing dan relevansinya. Penelitian ini bertujuan mengidentifikasi langkah-langkah penting pengembangan prodi dari aspek input, proses, dan output. Dengan menggunakan metode deskriptif kualitatif pendekatan pengembangan, data dikumpulkan melalui observasi, wawancara mendalam, angket, dan dokumentasi dari informan yang dipilih secara purposive meliputi pimpinan perguruan tinggi, ketua jurusan, dosen, dan mahasiswa. Hasil penelitian menemukan tujuh langkah strategis pengembangan aspek input, lima langkah untuk aspek proses, dan empat langkah untuk aspek output. Langkah kunci meliputi intensifikasi sosialisasi dan kolaborasi dengan kantor kementerian agama kabupaten, penyusunan kurikulum khas yang menekankan kompetensi administrasi dan manajemen, prioritas dosen berlatar belakang manajemen pendidikan, perluasan PPL mencakup supervisi dan konseling, serta kebijakan politis prospektif terkait format ijazah. Penelitian menyimpulkan bahwa kejelasan arah prodi—menghasilkan lulusan keguruan atau non-keguruan—bersifat fundamental, dengan rekomendasi rakor ev kurikulum dan pemformatan ijazah strategis untuk memastikan keterterimaan lulusan di pasar kerja.